2018
DOI: 10.1002/jsfa.9015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ethrel, 1‐MCP and modified atmosphere packaging on the quality of ‘Wonderful’ pomegranates during cold storage

Abstract: During long-term cold storage of this non-climacteric fruit, ethrel application induced endogenous ethylene biosynthesis, accelerating the appearance of CI symptoms in contrast to the observations made for MAP and 1-MCP treatments. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 64 publications
3
31
0
Order By: Relevance
“…e respiratory peaks of the MA fruits and the control fruits appeared at 15 days of storage in the experiment, and the peak of fruit was significantly delayed by MA+1-MCP treatment during storage, indicating a better effect of MA+1-MCP treatment than the others. is is consistent with the effects of MA+1-MCP treatment on pear [19], litchi [36], pomegranate [32], and other fruits. At the peak of ethylene, the ethylene production rate from the MA+1-MCP treatment was significantly lower than the other two treatment, which further demonstrated the good effect of MA+1-MCP treatment on fig fruit during postharvest storage.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…e respiratory peaks of the MA fruits and the control fruits appeared at 15 days of storage in the experiment, and the peak of fruit was significantly delayed by MA+1-MCP treatment during storage, indicating a better effect of MA+1-MCP treatment than the others. is is consistent with the effects of MA+1-MCP treatment on pear [19], litchi [36], pomegranate [32], and other fruits. At the peak of ethylene, the ethylene production rate from the MA+1-MCP treatment was significantly lower than the other two treatment, which further demonstrated the good effect of MA+1-MCP treatment on fig fruit during postharvest storage.…”
Section: Discussionsupporting
confidence: 87%
“…1-MCP + MA treatment significantly inhibited the increase in fruit MDA content, delayed or reduced cell membrane damage, and delayed fruit senescence. A similar situation was observed in the study of pomegranate by Valdenegro et al [32].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The fruits were harvested and selected on the basis of maturity, considering size, weight, color, and other quality parameters according to Valdenegro et al (2018) , before experimental treatments.…”
Section: Methodsmentioning
confidence: 99%
“…Simultaneously, as represented in Figure 2a, compared with HT and HT + 1-MCP treatment groups, the surface gloss of jujube fruits for the 1-MCP treatment group became disappeared, and even some of them began to rot in the later stage. Valdenegro et al (2018) found that 1 µl L −1 1-MCP could inhibit chilling injury of "wonderful" pomegranates during cold storage. Zhong and Xia (2007) also found that 600 nl L −1 1-MCP treatment could inhibit the degradation of chlorophyll and reduce the stem-end rot incidence of Indian jujube fruits during storage at room temperature.…”
Section: Effects Of Different Treatments On the Appearance Red Index And Color Of Jujube Fruits During Cold Storagementioning
confidence: 99%